Advances in atomic, molecular, and optical physics. - Inokuti, Mitio; Bederson, Benjamin; Walther, Herbert (Advances in atomic, molecular, and optical physics, 1994)
Addresses atomic collisions and identifies deficiencies. Exploring ways to improve the quality of cross-section data, this book focusses on cross-section determination by experiment or theory, on needs in selected applications, and on efforts toward the compilation and dissemination of data.